Nurettin Şazi Kösemihal'in Sosyoloji Anlayışı / The sociological viewpoint of Nurettin Shazi Kosemihal - Zavalsız, Yusuf Sinan (Journal of History Culture and Art Research, 2017)
Abstract In this article, we studied the sociological viewpoint of Nurettin Shazi Kosemihal who is one of the prominent scholars in the last term of Ottoman Empire and the early period of the Republic of Turkey and he bore witness to that time. At the very beginning, Kosemihal criticized Durkheim, then he mentioned the differences between the European and the American schools of sociologies. We tried to determine that which approach he supported from them. After we compared different methods, we found that he was in favour of the pluralist method. In this context, we also dealt with Gurvitch’s method that Kösemihal’s sociological viewpoint relies on and the sociometry of Moreno that Kosemihal had a pioneering role to introduce it to Turkey. Öz Bu makalede, imparatorluğun son dönemi ile cumhuriyetin ilk dönemine yakından tanıklık eden, Türk Sosyoloji Tarihi’nin önemli simalarından birisi olan Nurettin Şazi Kösemihal’in sosyoloji anlayışı üzerinde durulmuştur. İşe Durkheim’i eleştirmekle başlayan, daha sonra Avrupa ve Amerikan sosyoloji ekolleri arasındaki farklardan bahseden Kösemihal’in ağırlıklı olarak hangi tarafı tercih ettiği belirlenmeye çalışılmıştır. Simplist yöntem ile plüralist yöntemin mukayesesinden sonra Kösemihal’in tamamen plüralist yöntem tarafında durduğu ortaya konulmuştur. Bu bağlamda Kösemihal’in, plüralist yönteme dayanan, sosyoloji anlayışını oturttuğu Gurvitch metodu ile Türkiye’ye girmesine önayak olduğu Moreno’nun sosyometrisinden bahsedilmiştir.